Bestiary Movement in “The Dark Alleys” by I. A. Bunin - N. Y. Lozyuk (Научный диалог)
The article is devoted to the bestiary in “The Dark Alleys” by I. A. Bunin. The author draws attention to the fact that Bunin’s “The Dark Alleys” are densely populated by animals, birds, fish, reptiles, insects. A full list of the living things mentioned in the book is presented: horses, oxen, donkeys, goats, sheep, rabbits, dogs, leopard, elks, deer, rats, bat, hedgehog, frogs, eagles, owl etc. It is reported that the book used the 286 words with animalistic semantics. Zoomorphic imagery is considered as an important means of creating in fiction the integral image of the living Universe - an infinite universe in which all things are equal and related to each other. The author shows that the intensity of treatment to bestiary imagery throughout the book is uneven and undergoes big changes. It is noted that, only 4 of the 40 texts have absolutely no animal vocabulary. Attention is paid to the reflection of Bunin’s worldview and creative problems of the writer in the specifics of bestiary movement. For example, one of the artistic aims of the writer is to convey to the reader a sense of the overabundance of living life, which explains the considerable number of the verbal vocabulary in the text that describes the motion and movement of living beings. The analysis of the novel “A Night Stay” is presented.